A production system study of Threadknots Corporation - Tabamo, Rose Aimee J.; Dizon, Angelita Mendoza (1993.)
This study was patterned after an IE-151 Production Systems Study of a manufacturing and exporting company of jogging suits. It was conducted within the A.Y. 1990-1991 by a group of industrial engineering students of the University of the Philippines. Unlike the said study this was more of an observation as well as a participation research on THREADKNOTS, CORPORATION, a manufacturer/exporter of children's clothes and ladies blouses. Having worked as an apprentice in the factory, data were basically gathered through observation, participation in the production processes and through interviews with the management and personnel in particular the general manager, the Accountant, Purchaser, Import/export coordinator and Supervisor. The results of the data-gathering detailed the descriptions of the factory in terms of its operations - production processes, product design, organizational set-up and its performance such as production capacity, distribution of workforce, utilization of materials and equipment and the labor relationship between the management and the workers. In the process of the observation, participation and presentation of the company's descriptives, the following problems were noted: 1. Urgent need for capable individuals to perform key positions such as operations management (which of course entailed Production Planning and Inventory Control) and merchandising; 2. delays in delivery shipments due to not fully utilizing its plant capacity; and 3. need for production planning and inventory control to coordinate and maximize the utilization of the factors of production in order to produce goods in the demanded quantity and at the demanded time. The general recommendations were the following: 1. Line balancing - plan to arrange for an even flow of production within a work station such that operations are made approximately of equal time duration and that there is a correct number of people working on a certain operation to finish the required output maintained from preceeding operations. This would need accurate time and motion studies, knowledge of the capacity of every worker and properly sequenced operations breakdown. 2. Tap human resources the factory has in order to perform the needed jobs. If need be, train them. Acquaint them with the detailed responsibilities that their jobs require. Instruct them on methods of applying their jobs in the actual operations of the factory. 3. The study presented methods of production scheduling, capacity planning computation and line balancing application based on common practices of some garment manufacturing companies to serve as guides in the practice of production planning and control.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Thread